Polish Underground Extracts, no. 6 (1985) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Extracts from Polish underground publications compiled and translated into English by the RFE Polish Publication Unit for broadcasting purposes. Introductions to most articles are provided by RFE staff, and items are compiled in issues based mainly on theme and date. Repeated Women's Strikes at the Rosa Luxemburg Factory in Warsaw[from: Tygodnlk Mazowsze, no. 121 (14 March 1985) and Tygodnlk Mazowsze, no. 122 (21 March 1985)]The following two reports appeared in the Warsaw underground Solidarity weekly. They describe recent strikes that have taken place in connection with the price rises introduced by the government in March this year and the working conditions at the Rosa Luxemburg light bulb factory, where the majority of employees are women. Let's Not Kid Ourselves: An Interview with an Honest Director[from: Bez Dekretu, no. 1 (November 1984)]This is an interview with one of the few nonparty-member directors of a small industrial plant. He condemns the running of the economy in Poland, at the same time sparing no criticism of certain aspects of Solidarity and the general attitude of the Polish working man. "Bez Dekretu" [Without Edict] is an independent journal published in Kraków.